SIGNIFICANCE OF THE LITERARY TEXT AS A PROCESS - Mladenoski, Ranko (PALIMPSEST / ПАЛИМПСЕСТ, 2019)
This paper is an overview of an important book written by the eminent author Venko Andonovski, whose relevance remains to this day, primarily because the book elaborates the essential questions from the theory of literature and literary criticism related to the process of discovering the significance of literary works, but also because the book contains very successful and insightful interpretations of many Macedonian literary works and authors. Namely, the book titled "Text Processes" is composed of four parts with numerous essays and literary analyzes. In our review, the methods with which Andonovski performs literary-theoretical and literary-critical elaborations are described in details, but also value judgments are offered for the texts that are published, i.e., republished in this book. In the conclusion of the article it is emphasized that Andonovski’s book "Text Processes" offers not only fascinating theses for the general approach to discovering the meaning and the significance of the literary work, but a very solid and demonstrative practical analyzes of specific literary and artistic texts as well, that will open new perspectives to the careful reader in acquiring interpretation skills, and that is what makes this book relevant and attractive for today’s expert readership.